Student Mental Health In The School Environment: Psychological Challenges And Solutions - Dewi flower Rose; Ummi Masrufah Maulidiyah; Abdul Basit; Jamiatul Laila; Shalwa Hauzy Azzara (P3I UMSurabaya, 2025)
Student mental health has recently become a major concern in modern education. Mental health plays a crucial role in students emotional, social, and academic development. However, the school environtment often presents a source of stress due to academic pressure, complex social relationship between students. Therefore, strategic steps are needed, such as increasing the role of guidance counselors, implementing a curriculum that is more adaptive to students psycological needs, and strengthening mental health literacy program in school. By creating a mentally healty learning environtment, student are expected to be able to develop their potential optimally and be empowered to face academic and social challenges. This research focuses on identifiying the main callenges students face in maintaining mental health in the school environment and formulating various strategies and solutions, ranging from students experiencing psycological problems.